PERAN LEMBAGA PEMBERDAYAAN MASYARAKAT DALAM PENANGANAN SAMPAH RUMAH TANGGA BERDASARKAN PERDA NO 2 TAHUN 2011 DI KELURAHAN RAWA MAKMUR KOTA BENGKULU - marleni, wisuda andeka; nesa, Pujja afria; Sumaryono, Dino (Jurnal Sanitasi Profesional Indonesia, 2024)
Waste management activities cannot be separated from the role of the Community Empowerment Institution. At this point in time, the Community Empowerment Institution's attempts to control waste are still on the lower end of the spectrum. Infrastructure that is not appropriate is a significant obstacle to effective waste management. When it comes to the collection and classification of household waste, the overriding objective of our research is to determine whether or not the Local Waste Management (LPM) of Rawa Makmur Village in Bengkulu City conforms with Regional Regulation No. 2 of 2011. In this particular study, a qualitative research methodology was used. The findings are provided in their entirety as descriptive data, which was compiled via in-depth interviews with several reputable sources. For the purpose of this investigation, a total of eight individuals were questioned; four of the primary informants for this research were members of Community Empowerment Institutions, while four more individuals functioned as supporting informants. Based on the findings, it was determined that the informants had effectively completed the mission assigned to them by the Community Empowerment Institution, which was to collect garbage from households. However, the Community Empowerment Institution is not operating as efficiently as it might be due to the fact that the Environmental Service still has certain weaknesses in terms of its infrastructure and facilities. It is recommended that the leadership of the Environmental Service evaluate and improve facility infrastructure for waste collection and sorting so that Community Empowerment Institution can carry out its duties and roles according to Regional Regulation No. 2 of 2011 without any obstacles. Keywords: Role; Community Empowerment Institution; Waste Handling